Effect of the COVID-19 Pandemic on Emergency Department Presentations with Mushroom Poisoning: A Report from Turkey - Özdemir, Serdar; Altunok, İbrahim; Özkan, Abuzer; Algın, Abdullah; Akça, Hatice Şeyma; Aksel, Gökhan; Eroğlu, Serkan Emre (Avicenna Journal of Medicine, 2022)
Background In this study, we investigated the effect of the coronavirus disease 2019 (COVID-19) pandemic on emergency department admissions with mushroom poisoning in a tertiary hospital in Turkey.Materials and Methods This study was conducted as a retrospective cohort study to evaluate the data of patients admitted to the emergency department between January 1, 2018, and December 31, 2020. The patients diagnosed with the International Classification of Diseases-10 code T62.0 concerning the toxic effect of ingested mushrooms were identified through the computerized medical and laboratory record system of the hospital. The patients' demographic data, presentation seasons, laboratory findings, emergency department outcomes, and mortality due to mushroom poisoning were obtained. To reveal the effect of COVID-19 pandemic on emergency department presentations with mushroom poisoning, the means of the pre-pandemic period (2018–2019) and the pandemic period (2020) were compared.Results The data of a total of 171 patients were included in the final analysis. The number of patients diagnosed with the toxic effect of ingested mushrooms was 96 in 2018, 61 in 2019, and 14 in 2020. There was a 5.6-fold decrease during pandemic period in the number of patients presenting to the emergency department with mushroom poisoning.Conclusion The decrease in mushroom poisoning cases may be related to the changes in the eating habits of individuals during the pandemic and our study being conducted in a metropolitan city. We recommend that multicenter studies be performed to verify the data obtained from our study and increase their generalizability.
Keywords: mushroom poisoning; poisoning; coronavirus disease 2019; toxic